Blood parasitic diseases and specific immune responses - Musoke, A.J.; Masake, R.A. (Office International des Epizooties, 1997)
Specific humoral and cell mediated immunity to blood parasites is reviewed. There is a table detailing the worldwide occurrence of economically important blood parasitic diseases followed by summaries of immunological aspects of trypanosomosis, theileriosis, babesiosis, anaplasmosis, cowdriosis and ehrlichiosis.